READING GENDER RELATIONS AND SEXUALITY: PRETEENS SPEAK OUT - Moffatt, Lyndsay; Norton, Bonny (Canadian Journal of Education/Revue canadienne de l'éducation, 2008)
Recent research has documented the persistence of unequal gender relations and homophobia in young people’s lives. Feminist post‐structural theories of gender and socio‐cultural theories of learning suggest educators need to understand students’ constructions of gender relations, masculine/feminine desires, and sexuality if they hope to challenge these behaviors. In this article, we examine a diverse group of 47 preteens’ constructions of gender relations, masculine/feminine desires, and sexuality, using a survey, a story from the popular comic Archie, and individual interviews. We found that although participants produced feminist and patriarchal constructions of gender relations, they constructed masculine and feminine sexuality as uniformly heterosexual. Key words: popular culture, feminism, adolescents, discourse analysis Des recherches récentes indiquent la persistance de relations inégales entre les hommes et les femmes et de l’homophobie chez les jeunes. Des théories d’apprentissage poststructuralistes féministes au sujet du genre ainsi que des théories socioculturelles donnent à penser que les pédagogues ont besoin de comprendre les constructions que se font les élèves des relations entre les sexes, des désirs masculins et féminins et de la sexualité s’ils espèrent remettre en question ces comportements. Dans cet article, les auteures analysent, à l’aide d’un sondage, d’une histoire tirée de la bande dessinée Archie et d’entrevues individuelles, un éventail diversifié de 47 constructions que se font des préadolescents des relations entre les sexes, des désirs masculins et féminins et de la sexualité. Elles ont découvert que les participants ont produit des constructions féministes et patriarcales des relations entre les sexes, mais hétérosexuelles de la sexualité masculine et féminine. Mots clés : culture populaire, féminisme, adolescents, analyse des discours